Equity in Mental Health Services for Youth at Clinical High Risk for Psychosis: Considering Marginalized Identities and Stressors. Issue 2 (3rd April 2022) - DeLuca, Joseph S.; Novacek, Derek M.; Adery, Laura H.; Herrera, Shaynna N.; Landa, Yulia; Corcoran, Cheryl M.; Walker, Elaine F.
ABSTRACT: Prevention and early intervention programs have been initiated worldwide to serve youth at Clinical High Risk for Psychosis (CHR-P), who are adolescents and young adults experiencing subclinical psychosis and functional impairment. The primary goals of these efforts are to prevent or mitigate the onset of clinical psychosis, while also treating comorbid issues. It is important to consider issues of diversity, equity, and inclusion in CHR-P work, especially as these programs continue to proliferate around the world. Further, there is a long history in psychiatry of misdiagnosing and mistreating psychosis in individuals from racial and ethnic minority groups. Although there have been significant developments in early intervention psychosis work, there is evidence that marginalized groups are underserved by current CHR-P screening and intervention efforts. These issues are compounded by the contexts of continued social marginalization and significant mental health disparities in general child/adolescent services. Within this narrative review and call to action, we use an intersectional and minority stress lens to review and discuss current issues related to equity in CHR-P services, offer evidence-based recommendations, and propose next steps. In particular, our intersectional and minority stress lenses incorporate perspectives for a range of marginalized and underserved identities related to race, ethnicity, and culture; faith; immigration status; geography/residence; gender identity; sexual orientation; socioeconomic status/class; and ability status.